PUBLIC SPEAKING WITH PRACTICE AND PREPARATION METHODS AT MAAHAD DARUL AZHAR WAL HIKMAH TERENGGANU, MALAYSIA - Anggrayni, Dewi; Permana, Indra Martian; Anshari, Muhammad Dzaki; Hamid, Ruslan; Jabar, Abdul (LPPM Univ. Ibn Khaldun Bogor, 2025)
Failure to understand information in the learning process often occurs due to weak public speaking skills, especially in the school environment. To anticipate this problem, they needs some method as to increase they skills in public speakings. The Postgraduate of Islamic Communication and Broadcasting UIKA conducts community service activities at Mahaad Darul Azhar Wal Hikmah Malaysia by providing public speaking training based on Practice and Preparation. This method is effectively applied to programs with a short duration time, with hope of having a sustainable effect and beneficial for students to confidently carry out da'wah practices in the community. This activity provides theory and practice of public speaking with the